내측 반월연골판 낭종으로 오인된 활액막 혈관종 - 민경대(Kyoung-Dae Min); 조휘제(Whi-Je Cho); 차주영(Joo-Young Cha) (The journal of the Korean Orthopaedic Association, 2022)
활액막 혈관종은 주로 슬관절에서 발견되는 일종의 혈관 기형으로 알려져 있다. 저자들은 37세 남자에서 내측 반월연골판 낭종으로 오인할 수 있는 활액막 혈관종을 경험하여 진단적 초음파 소견과 함께 관혈적 절제 후 반월연골판 봉합술의 임상적 결과를 보고하고자 한다. Synovial hemangioma is a vascular malformation that usually involves the knee. This paper presents the diagnostic ultrasound findings of a synovial hemangioma that could be mistaken for a medial meniscus cyst in a 37-year-old man and report the clinical result of the meniscal repair after an open excision. KCI Citation Count: 1